A211 IMPACT OF A GAME-BASED LEARNING INTERVENTION IN SIMULATION-BASED ENDOSCOPY TRAINING ON COLONOSCOPY PERFORMANCE IN NOVICE ENDOSCOPISTS - A RANDOMIZED CONTROLLED TRIAL. (15th March 2019) - Satchwell, J B; Scaffidi, M A; Gimpaya, N; Li, J; Khan, R; Walsh, C M; Pearl, M; Winger, K; Kalaichandran, R; Lin, P; Grover, S C
Abstract: Background: Simulation-based training (SBT) curricula for training novices in gastrointestinal endoscopy has been shown to be effective. Gamification, which is the application of game-design elements such as competition, rankings and rewards, has been used to enhance procedural learning in healthcare, but no studies have investigated the effects of a comprehensive gamification curriculum on the acquisition of endoscopic skills amongst novice endoscopists. Aims: To evaluate a SBT curriculum using gamification for novice endoscopists on the performance of simulated and clinical colonoscopies, compared to a conventional SBT curriculum. Methods: Thirty-six novice endoscopists (who had completed <20 previous colonoscopies) from the general surgery and gastroenterology programs at the University of Toronto participated. Participants were randomized into the Conventional Curriculum (CC ) or the Gamified Integrated Curriculum (GIC) Group . Both groups received 6 hours of one-on-one simulation training on two simulator models, a benchtop and EndoVR® model, augmented with expert feedback, interlaced with 4 hours of small group teaching on theory of colonoscopy. The GIC group had curriculum integrated with game-design elements: a leaderboard summarizing participant performance, game narrative, achievement badges, and rewards for top performance. Performance was assessed on the simulator prior to training, immediately after training, and 4–6 weeks after training. Transfer of skills were assessed during two clinical colonoscopies between 4–6 weeks post training by blinded independent expert endoscopists. The primary outcome measure was the difference in colonoscopic performance between the two groups using validated assessment tools measuring cognitive, technical and integrative skills, including the Joint Advisory Group for GI Endoscopy Direct Observation of Procedural Skills (JAG DOPS), and the Gastrointestinal Endoscopy Competency Assessment Tool (GiECAT). Results: The gamification group outperformed the control group in global performance for the first two clinical colonoscopies as measured by JAG DOPS (F1, 37 =12.89, P = 0.001 ) and GiECAT ( F1, 34 = 12.55; P = 0.001). Conclusions: We found that a SBT curriculum using gamification for colonoscopy was associated with significantly improved global performance among novice endoscopists. It is an instructional strategy with potential to enhance learning. Global performance as measured by JAG DOPS at clinical colonoscopies. Funding Agencies: CAGAbbVie Centre of Excellence in Continuing Health Education [grant number:2017 CAG-ABBVIE-ERG]